Estradiol-dependent perforin expression by human regulatory T-cells - Valor, Larissa; Teijeiro, Roseta; Aristimuño, Carol; Faure, Florence; Alonso, Bárbara; de Andrés, Clara; Tejera, Marta; López-Lazareno, Nieves; Fernández-Cruz, Eduardo; Sánchez-Ramón, Silvia (European journal of clinical investigation, 2011)
Eur J Clin Invest 2011; 41 (4): 357–364 Background CD4+CD25+FoxP3+ regulatory T‐cells (nTReg) have been shown to suppress immune responses to autoantigens and to other diverse antigens, this suppression is mainly mediated by a cell contact‐dependent mechanism not yet fully defined. It has been reported that both human natural and induced TReg exert cytotoxic activity against autologous target cells, which suggests that the perforin/granzyme pathway may be a relevant candidate mechanism for the suppressive function of TReg. Previous reports have shown that oestradiol (E2) modulates TReg percentages and function. Methods  We have evaluated in pregnant and non‐pregnant subjects perforin intracellular expression in CD4+CD25+FoxP3+ regulatory T‐cells by flow cytometry in whole blood, ex‐vivo purified nTReg and ex‐vivo purified nTReg after TCR and E2 stimulation. The expression of cellular degranulation markers was also phenotypically determined. Results  We show that E2 expands TReg, enhances in vitro TReg function and induces a TReg phenotype in activated responder (CD4+CD25) T‐cells, further increasing the expression of perforin on TReg than in vitro T‐cell receptor activation alone. We found surface lysosomal‐associated membrane glycoproteins (LAMP)‐1and LAMP‐2 expression by TReg, which is a sign of cell degranulation and therefore of cytotoxicity exerted by these cells. Conclusion  Our data demonstrates the presence of functional TReg cytotoxic properties in biological systems and support the concept that E2 enhances the number and function of TReg suggesting the potential interaction between E2 and immunoregulatory mechanisms.